Indifference to Riba Practices: Using "Epistemology of Ignorance" to Understand Customer Behavior in Conventional General Banking - Bisri, Hasan (Madania: Jurnal Kajian Keislaman, 2023)
This research seeks to elaborate on using the epistemology of ignorance to understand the phenomenon of conventional general banking customer behavior. This descriptive research is based on quantitative data and then explored qualitatively. Quantitative data was collected by questionnaire from 46 participants. Apart from questionnaires, data was also obtained by interviews. Data from the interviews were used to deepen the qualitative analysis. The research results show that choosing not to become a Sharia banking customer is a phenomenon that the epistemology of ignorance can explain. A person who believes that bank interest is included in the usury category but is reluctant to become a Sharia banking customer, one of the reasons is because he is hiding behind an epistemology of ignorance. They exploit ignorance as a resource that allows knowledge to be distorted, obscured, hidden, or magnified. Ignorance becomes a strategy to avoid, hide, or make knowledge about usury unreliable. They know that bank interest is included in the category of usury and realize that usury is prohibited, but they pretend not to know and ignore their knowledge. Penelitian ini berupaya mengelaborasi penggunaan epistemologi ketidaktahuan untuk memahami fenomena perilaku nasabah perbankan umum konvensional. Penelitian deskriptif ini berbasis pada data kuantitatif yang kemudian didalami secara kualitatif. Data kuantitatif dikumpulkan dengan kuesioner dari 46 partisipan. Selain dengan kuesioner, data-data juga diperoleh dengan wawancara. Data hasil wawancara itu dimanfaatkan untuk menperdalam analisis secara kualitatif. Hasil penelitian menunjukkan bahwa memilih untuk tidak menjadi nasabah perbankan Syariah adalah fenomena yang bisa dijelaskan dengan epistemologi ketidaktahuan. Seseorang yang memiliki keyakinan bahwa bunga bank termasuk kategori riba tetapi enggan menjadi nasabah perbankan Syariah, salah satunya karena berlindung di balik epistemologi ketidaktahuan. Mereka memanfaatkan ketidaktahuan sebagai sumber daya yang memungkinkan pengetahuan dibelokkan, dikaburkan, disembunyikan atau diperbesar. Ketidaktahuan menjadi semacam strategi untuk menghindari, menyembunyikan, atau menjadikan pengetahuan tentang riba menjadi tidak dapat diandalkan. Mereka tahu bunga bank termasuk kategori riba dan menyadari bahwa riba dilarang, tetapi mereka pura-pura tidak tahu dan mengabaikan pengetahuannya.